Pengembangan Model Pembelajaran PAI Berbasis Nilai-Nilai Wasaṭiyah dalam Beragama pada Siswa SMP - Siti Nur Chamidah; Muna Yastuti Madrah; Agus Irfan (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2022)
The purpose of this study is to describe the learning model of Islamic Religious Education (PAI) based on wasaṭiyah values in religion and to determine the strategy for developing wasaṭiyah values in religion to characterize the attitudes of students at the junior high school (SMP) level. This study uses a qualitative approach, a research study at SMPN 1 Tayu, Pati district, Central Java province. Data were collected by using observation, interview and documentation techniques. In conducting the analysis using a qualitative descriptive approach, focusing on one object, namely how PAI teachers develop PAI learning models based on wasaṭiyah values in religion. The age of junior high school students is categorized as adolescence, which is the phase when they begin to leave childhood and are heading to adulthood. In this phase, adolescents seek a more established identity through exploration of themselves and their social environment. In this important phase, it is necessary to instill wasaṭiyah values in religion, especially in heterogeneous environments. The results of the research, in the development of the PAI learning model based on wasaṭiyah values by PAI teachers by combining several learning models by experts and several approaches whose use is adapted to the material and needs of students, plus applying the four wasaṭiyah values, namely tolerance, justice, balance and equality. Development efforts in applying wasaṭiyah values into character attitudes and behavior of students are supported by several activities that support the application of wasaṭiyah values in religion that are in accordance with the principles of inculcating character values, namely providing knowledge, changing the environment and exemplary as well as through good communication